KAJIAN ATAS HASIL-HASIL PENELITIAN KAWASAN KONSERVASI DAERAH RESAPAN AIR DI CEKUNGAN BANDUNG - Mardi Wibowo (Jurnal Teknologi Lingkungan, 2005)
Development of city and population in Bandung Basin cause the need ofclean water is increasing too. The increasement of groundwater abstraction andthe decreasement of recharge area will disturb the natural water balance in the Bandung Basin. Therefore, recharge area of the Bandung Basin must be protected and conserved. The efforts to protected this area is done with make some regulation and policy to protect and conserved the recharge area and mapping (delineation) recharge area. Generally the regulation is good enough, but this isn’t detail; and monitoring and inforcement in field is still very weak. From the results of the research that were done, the recharge area in Bandung basin is in the northen and southern part of Bandung Basin with elevation more than 750 m. Detil mapping and delineation of recharge area with scale 1 : 100.000 or 1 : 5.000 must be done as soon as possible.